Trillion Game. Volume 8 - Inagaki, Riichiro (Viz signature., 2025)
"Self-proclaimed "world's greediest man" Haru and timid computer whiz Gaku set out to make a trillion dollars. They start the company Trillion Game to accomplish this task and hope to iron out the details as they go. With charm, technical skills, and no business plan, can these unlikely friends reach their lofty goal? Haru and Gaku have managed to put Trillion TV in the black. Meanwhile, Kirihime uses her massive capital as a weapon to fight back. But Haru's shocking response leads to the beginning of a Trillion Game tightrope walk!" --